Non‐canonical activation of CREB mediates neuroprotection in a Caenorhabditis elegans model of excitotoxic necrosis. Issue 4 (20th December 2018) - Feldmann, K. Genevieve; Chowdhury, Ayesha; Becker, Jessica L.; McAlpin, N'Gina; Ahmed, Taqwa; Haider, Syed; Richard Xia, Jian X.; Diaz, Karina; Mehta, Monal G.; Mano, Itzhak
Abstract: Excitotoxicity, caused by exaggerated neuronal stimulation by Glutamate (Glu), is a major cause of neurodegeneration in brain ischemia. While we know that neurodegeneration is triggered by overstimulation of Glu‐receptors (GluRs), the subsequent mechanisms that lead to cellular demise remain controversial. Surprisingly, signaling downstream of GluRs can also activate neuroprotective pathways. The strongest evidence involves activation of the transcription factor cAMP response element‐binding protein (CREB), widely recognized for its importance in synaptic plasticity. Canonical views describe CREB as a phosphorylation‐triggered transcription factor, where transcriptional activation involves CREB phosphorylation and association with CREB‐binding protein. However, given CREB's ubiquitous cross‐tissue expression, the multitude of cascades leading to CREB phosphorylation, and its ability to regulate thousands of genes, it remains unclear how CREB exerts closely tailored, differential neuroprotective responses in excitotoxicity. A non‐canonical, alternative cascade for activation of CREB‐mediated transcription involves the CREB co‐factor cAMP‐regulated transcriptional co‐activator (CRTC), and may be independent of CREB phosphorylation. To identify cascades that activate CREB in excitotoxicity we used a Caenorhabditis elegans model of neurodegeneration by excitotoxic necrosis. We demonstrated that CREB's neuroprotective effect was conserved, and seemed most effective in neurons with moderate Glu exposure. We found that factors mediating canonical CREB activation were not involved. Instead, phosphorylation‐independent CREB activation in nematode excitotoxic necrosis hinged on CRTC. CREB‐mediated transcription that depends on CRTC, but not on CREB phosphorylation, might lead to expression of a specific subset of neuroprotective genes. Elucidating conserved mechanisms of excitotoxicity‐specific CREB activation can help us focus on core neuroprotective programs in excitotoxicity. Cover Image for this issue: doi:10.1111/jnc.14494 . Abstract : Excitotoxicity is a major cause of neurodegeneration in brain ischemia, and the transcription factor cAMP response element‐binding protein (CREB) mediates neuroprotection in excitotoxicity. Canonical views describe CREB as triggered by phosphorylation, but the wide use of this mechanism makes it unclear how CREB exerts specific neuroprotective responses. We use a model of excitotoxic necrosis in C. elegans, and show that a conserved mechanism in CREB activation in excitotoxic necrosis involves a CREB co‐factor (CRTC) and is independent of CREB phosphorylation. Using this non‐canonical mechanism of CREB activation might lead to expression of a specific subset of neuroprotective genes in excitotoxicity. Cover Image for this issue: doi:10.1111/jnc.14494 .